High-rate lithium ion battery positive electrode material as well as preparation method and application thereof

By forming a composite cladding layer of carbon and oxide solid electrolyte on the surface of the positive electrode material of the lithium-ion battery, the problem that the cladding layer in the prior art is not conducive to lithium ion or electron transmission, and the high rate performance and cycle stability of the lithium-ion battery are achieved.

CN119890245APending Publication Date: 2025-04-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202311391734.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The cladding layer of the positive electrode material of the existing lithium-ion battery is not conducive to the transmission of lithium ions or electrons, and affects the rate performance.

Method used

A composite cladding layer formed by carbon and oxide solid electrolyte is used to form a high-magnification lithium-ion battery positive electrode material by mixing the carbon source material, oxide solid electrolyte and positive electrode active material on the surface of the positive electrode active material in a certain proportion.

Benefits of technology

The rate performance and cycle stability of the positive electrode active material are enhanced, and the good rate performance and cycle stability of lithium-ion batteries are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890245A_ABST
    Figure CN119890245A_ABST
Patent Text Reader

Abstract

The invention discloses a high-rate lithium ion battery positive electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: placing a carbon source material, an oxide solid electrolyte, a positive electrode active material and a solvent in stirring equipment, and uniformly stirring and mixing to obtain a mixed solution; placing the mixed solution in drying equipment, and performing drying treatment to obtain a precursor material; and placing the precursor material in sintering equipment, presintering for 2-6 hours at 150-300 DEG C, removing redundant solvent, continuously heating to 400-900 DEG C, preserving heat and sintering for 6-24 hours, and cooling to room temperature to obtain the high-rate lithium ion battery positive electrode material. The lithium ion battery positive electrode material prepared by the invention has a composite coating layer formed by carbon and oxide electrolyte, and when the lithium ion battery positive electrode material is applied to a lithium ion battery, the battery can have good rate capability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a high-rate lithium-ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are a type of energy storage device that is different from traditional energy sources and dominate the energy storage field. The cathode material of lithium-ion batteries plays a vital role and directly affects the battery's cycle performance and rate performance. Therefore, it is of great significance to carry out research on cathode material modification.

[0003] In order to improve the cycle performance and rate performance of positive electrode materials, one of the main technical means is surface coating. At present, the coating materials mainly include zirconium dioxide, aluminum phosphate, aluminum oxide and magnesium oxide, or a single carbon layer or electrolyte layer coating. However, the presence of the above coating layers is not conducive to the transmission of lithium ions or electrons, thereby affecting the rate performance of the positive electrode material. Summary of the invention

[0004] The purpose of the present invention is to provide a high-rate lithium-ion battery positive electrode material and a preparation method and application thereof, so as to solve the problem that the coating layer of the existing positive electrode material is not conducive to the transmission of lithium ions or electrons, thereby affecting the rate performance. The lithium-ion battery positive electrode material provided by the present invention has a composite coating layer formed by carbon and oxide electrolyte. When applied to a lithium-ion battery, the battery can have good rate performance and cycle stability.

[0005] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a high-rate lithium-ion battery positive electrode material, the preparation method comprising:

[0006] Placing the carbon source material, the oxide solid electrolyte, the positive electrode active material and the solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution;

[0007] placing the mixed solution in a drying device for drying to obtain a precursor material;

[0008] The precursor material is placed in a sintering device, pre-sintered at 150°C-300°C for 2 hours-6 hours, and after removing excess solvent, the temperature is further raised to 400°C-900°C, and sintered at this temperature for 6 hours-24 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained;

[0009] The positive electrode active material includes: one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials.

[0010] Preferably, the particle size Dv50 of the positive electrode active material is between 0.3 μm and 50 μm;

[0011] The carbon source material includes: one or more of carbon fiber, carbon nanotube, graphene, sucrose, starch, graphite, phenolic resin, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, epoxy resin; the particle size Dv50 of the carbon source material is between 100nm and 800nm;

[0012] The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte; the particle size Dv50 of the oxide solid electrolyte is between 100nm and 800nm;

[0013] The solvent includes: one or more of deionized water, ethanol, N-methylpyrrolidone, acetone, chloroform, benzene, styrene, and tetrahydrofuran;

[0014] The mass ratio of the positive electrode active material, the carbon source material and the oxide solid electrolyte material in the mixed solution is [0.65-0.95]: [0.001-0.2]: [0.001-0.2];

[0015] The solid content of the mixed solution is 10%-65%.

[0016] Preferably, the stirring equipment includes: one or more of a VC high-efficiency mixer, a magnetic stirrer, a vertical stirring tank, a high-speed mixer, and a planetary stirring mixer.

[0017] Preferably, the drying equipment includes: one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying treatment temperature is 60°C-300°C; and the drying time is 6 hours-24 hours.

[0018] Preferably, the sintering equipment includes: any one of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln;

[0019] The heating rate of the sintering equipment is set at 2°C / min-10°C / min.

[0020] In a second aspect, an embodiment of the present invention provides a high-rate lithium-ion battery positive electrode material prepared by the preparation method described in the first aspect, wherein the high-rate lithium-ion battery positive electrode material comprises a positive electrode active material, and a composite coating layer coated on the outer surface of particles of the positive electrode active material; the composite coating layer comprises carbon and an oxide solid electrolyte;

[0021] The positive electrode active material includes: one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials.

[0022] Preferably, the mass of the carbon accounts for 0.1%-20% of the total mass of the lithium-ion battery positive electrode material;

[0023] The mass of the oxide solid electrolyte accounts for 0.1%-20% of the total mass of the lithium-ion battery positive electrode material;

[0024] The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte.

[0025] In a third aspect, an embodiment of the present invention provides a positive electrode plate, which includes the high-rate lithium-ion battery positive electrode material described in the second aspect, a conductive agent and a binder.

[0026] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet, the negative electrode sheet, the electrolyte or the solid electrolyte, and the separator as described in the third aspect above.

[0027] Preferably, the lithium-ion battery comprises any one of a liquid lithium-ion battery, a condensed lithium-ion battery, a polymer lithium-ion battery or an all-solid-state lithium-ion battery.

[0028] The embodiment of the present invention provides a high-rate lithium-ion battery positive electrode material and a preparation method and application thereof. The high-rate lithium-ion battery positive electrode material is obtained by mixing a carbon source material and an oxide solid electrolyte in a certain proportion and coating them on the surface of a positive electrode active material to form a composite coating layer; the high-rate lithium-ion battery positive electrode material can simultaneously give play to the good ionic conductivity of the oxide solid electrolyte and the good electronic conductivity of carbon, thereby enhancing the rate performance of the positive electrode active material; the high-rate lithium-ion battery positive electrode material of the present invention is applied to a lithium-ion battery, so that the battery has good rate performance and cycle stability.

[0029] The preparation method provided by the embodiment of the present invention is simple to operate, can be applied to large-scale production, and has practical significance for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0031] Figure 1 It is a flow chart of a method for preparing a high-rate lithium-ion battery positive electrode material provided by an embodiment of the present invention.

[0032] Figure 2 It is a cycle curve diagram of button batteries assembled in Example 1 of the present invention and Comparative Example 1.

[0033] Figure 3 It is a rate performance curve diagram of button cells assembled in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0035] The embodiment of the present invention provides a high-rate lithium-ion battery positive electrode material including a positive electrode active material and a composite coating layer coated on the outer surface of particles of the positive electrode active material; the composite coating layer includes carbon and an oxide solid electrolyte.

[0036] The positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials; the particle size Dv50 of the positive electrode active material is between 0.3 μm and 50 μm.

[0037] The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte.

[0038] In the composite coating layer, the carbon is a single carbon particle, and the mass of the carbon accounts for 0.1%-20% of the total mass of the positive electrode material of the lithium ion battery, preferably 0.5%-8%; the mass of the oxide solid electrolyte accounts for 0.1%-20% of the total mass of the positive electrode material of the lithium ion battery, preferably 0.5%-8%; the carbon particles and the oxide solid electrolyte particles are in contact with each other, and there are gaps between some particles and the oxide solid electrolyte particles, and the composite coating layer covers the entire outer surface of the positive electrode material.

[0039] The present invention provides a method for preparing the above-mentioned high-rate lithium-ion battery positive electrode material, such as Figure 1 As shown, the specific steps include:

[0040] Step 110, placing the carbon source material, the oxide solid electrolyte, the positive electrode active material and the solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution;

[0041] The positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials; the particle size Dv50 of the positive electrode active material is between 0.3 μm and 50 μm;

[0042] The carbon source material includes one or more of carbon fiber, carbon nanotube, graphene, sucrose, starch, graphite, phenolic resin, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, and epoxy resin; the particle size Dv50 of the carbon source material is between 100nm and 800nm;

[0043] The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte; the particle size Dv50 of the oxide solid electrolyte is between 100nm and 800nm;

[0044] The solvent includes: one or more of deionized water, ethanol, N-methylpyrrolidone, acetone, chloroform, benzene, styrene, and tetrahydrofuran;

[0045] The mass ratio of the positive electrode active material, the carbon source material and the oxide solid electrolyte material in the mixed solution is [0.65-0.95]: [0.001-0.2]: [0.001-0.2];

[0046] The solid content of the mixed solution is 10%-65%;

[0047] The stirring equipment includes: one or more of a VC high-efficiency mixer, a magnetic stirrer, a vertical stirring tank, a high-speed mixer, and a planetary stirring mixer; the stirring equipment used in the present invention and the time required for stirring do not need to be particularly limited, and can be sufficient to mix the materials evenly.

[0048] Step 120, placing the mixed solution in a drying device for drying to obtain a precursor material;

[0049] The drying equipment includes one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying temperature is 60°C-300°C; and the drying time is 6 hours-24 hours.

[0050] Step 130, placing the precursor material in a sintering device, pre-sintering at 150° C.-300° C. for 2 hours-6 hours, removing excess solvent, continuing to heat to 400° C.-900° C., sintering at this temperature for 6 hours-24 hours, and cooling to room temperature to obtain a high-rate lithium-ion battery positive electrode material;

[0051] The sintering equipment includes: any one of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary furnace; the heating rate of the sintering equipment is set to 2°C / min-10°C / min; the present invention uses high-temperature sintering to carbonize the carbon source material to form a single carbon.

[0052] The high-rate lithium-ion battery positive electrode material prepared by the above preparation method of the present invention can be used to prepare positive electrode slurry together with a conductive agent and a binder, and then coated on a positive electrode collector and baked and dried to obtain a positive electrode plate. The positive electrode plate can be assembled into a lithium-ion battery with a negative electrode plate, an electrolyte or a solid electrolyte, and a separator.

[0053] The above-mentioned lithium-ion battery includes, but is not limited to: any one of a liquid lithium-ion battery, a condensed lithium-ion battery, a polymer lithium-ion battery or an all-solid-state lithium-ion battery.

[0054] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the high-rate lithium-ion battery positive electrode material of the present invention are respectively described below with multiple specific examples.

[0055] Example 1

[0056] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0057] (1) A total of 1 kg of carbon nanotubes and perovskite structure LLTO solid electrolyte powder (chemical formula Li 0.33 La 0.56 TiO3) and lithium cobalt oxide are used as raw materials, placed in a magnetic stirrer with deionized water, stirred and mixed evenly to obtain a mixed solution with a solid content of 30wt%; wherein the content of each material in the raw materials is: 8wt% of carbon nanotubes, 6wt% of perovskite structure LLTO solid electrolyte powder, and 86wt% of lithium cobalt oxide; the particle size Dv50 of lithium cobalt oxide is 15μm, the particle size Dv50 of perovskite structure LLTO solid electrolyte is 100nm; the particle size Dv50 of carbon nanotubes is 100nm.

[0058] (2) The mixed solution was placed in a forced air drying oven at 120° C. for 8 hours to obtain a precursor material.

[0059] (3) The precursor material is placed in a rotary furnace, heated to 200°C at a heating rate of 5°C / min, and the excess solvent is removed after pre-sintering for 4 hours. The temperature is then raised to 750°C at a heating rate of 5°C / min, and kept at this temperature for 15 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0060] The high-rate lithium-ion battery positive electrode material prepared in this embodiment is used to prepare positive electrode sheets and assembled into button batteries for testing. The specific process is as follows.

[0061] Preparation of positive electrode sheet: The high-rate lithium-ion battery positive electrode material, polyvinylidene fluoride (PVDF), and conductive carbon black (SP) prepared in this embodiment are homogenized into a slurry in a mass ratio of 90:5:5, and then coated on aluminum foil and dried to prepare a positive electrode sheet.

[0062] Assembly of button cells: Assemble button cells using conventional methods, including a positive electrode sheet coated with the high-rate lithium-ion battery positive electrode material prepared in this embodiment, a polypropylene PP separator, a graphite negative electrode sheet, and an electrolyte containing 1 mol / L LiPF6 (the solvent is ethylene carbonate).

[0063] The button battery test method is as follows: charge at a constant current rate of 1C to a voltage of 4.4V, then let it stand for 5 minutes, then discharge at a constant current rate of 1C to a voltage of 2.75V, and then let it stand for 5 minutes as a cycle charge and discharge process. Perform 100 cycles of charge and discharge tests according to the above method. The battery cycle curve is as follows: Figure 2 The cycle capacity retention rate after 100 cycles is shown in Table 1.

[0064] Example 2

[0065] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0066] (1) 1 kg of graphite and NASICON structure LAGP solid electrolyte powder (chemical formula: Li 1.5 Al 0.5 Ge 1.5 (PO4)3), lithium cobalt oxide is used as a raw material, and is placed in a magnetic stirrer with deionized water, stirred and mixed evenly to obtain a mixed solution with a solid content of 25%; wherein the content of each material in the raw material is: 6wt% graphite, 4wt% NASICON structure LAGP solid electrolyte powder, and 90wt% lithium cobalt oxide; the particle size Dv50 of lithium cobalt oxide is 10μm, the particle size Dv50 of NASICON structure LAGP solid electrolyte is 300nm; the particle size Dv50 of graphite is 300nm.

[0067] (2) The mixed solution was placed in a forced air drying oven at 120° C. for 12 hours to obtain a precursor material.

[0068] (3) The precursor material is placed in a rotary furnace, heated to 150°C at a heating rate of 5°C / min, and the excess solvent is removed after pre-sintering for 5 hours. The temperature is then raised to 800°C at a heating rate of 5°C / min, and kept at this temperature for 10 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0069] The high-rate lithium-ion battery positive electrode material prepared in this embodiment was used to prepare positive electrode sheets and assembled into button batteries for testing. The battery assembly and cycle testing methods were the same as in Example 1. The cycle capacity retention rate after 100 test cycles is shown in Table 1.

[0070] Example 3

[0071] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0072] (1) 1 kg of graphite and garnet structure LLZTO solid electrolyte powder (chemical formula: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ), lithium cobalt oxide as a raw material, placed in a magnetic stirrer with deionized water, stirred and mixed evenly to obtain a mixed solution with a solid content of 22%; wherein the content of each material in the raw material is: 8wt% of graphite, 7wt% of garnet structure LLZTO solid electrolyte powder, 85wt% of lithium cobalt oxide; the particle size Dv50 of lithium cobalt oxide is 20μm, the particle size Dv50 of garnet structure LLZTO solid electrolyte is 500nm; the particle size Dv50 of graphite is 500nm.

[0073] (2) The mixed solution was placed in a forced air drying oven and dried at 150° C. for 12 hours to obtain a precursor material.

[0074] (3) The precursor material is placed in a rotary furnace, heated to 200°C at a heating rate of 2°C / min, and the excess solvent is removed after pre-sintering for 3 hours. The temperature is then raised to 750°C at a heating rate of 2°C / min, and kept at this temperature for 10 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0075] The high-rate lithium-ion battery positive electrode material prepared in the embodiment of the present invention was homogenized with polyvinylidene fluoride (PVDF) and conductive carbon black (SP) in a mass ratio of 90:5:5 to form a slurry, and the positive electrode sheets were prepared and assembled into button batteries for testing. The battery assembly process was the same as the method in Example 1.

[0076] The method of the cycle test is the same as that of Example 1. The cycle capacity retention rate after 100 test cycles is shown in Table 1.

[0077] The rate performance of the button cell assembled in this embodiment was tested, and the specific method was as follows: first, the battery was charged to 4.4V at a 0.2C rate, and then the battery was kept at a constant voltage of 4.4V until the current decreased to 0.05C, and then the battery was discharged at a rate of 0.2C to 2.75V, and the cycle was repeated for 5 cycles; then the battery was charged to 4.4V at a rate of 0.5C, and then the battery was kept at a constant voltage of 4.4V until the current decreased to 0.05C, and then the battery was discharged at a rate of 0.5C to 2.75V, and the cycle was repeated for 5 cycles; then the battery was charged to 4.4V at a rate of 1C, and then the battery was kept at a constant voltage of 4.4V until the current decreased to 0.05C, and then the battery was discharged at a rate of 1C to 2.75V, and the cycle was repeated for 5 cycles; then the battery was charged to 4.4V at a rate of 2C, and then the battery was kept at a constant voltage of 4.4V until the current decreased to 0.05C, and then the battery was discharged at a rate of 2C to 2.75V, and the cycle was repeated for 5 cycles.

[0078] The rate cycle test diagram of the button cell of this embodiment 3 is as follows: Figure 3 shown.

[0079] Example 4

[0080] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0081] (1) 1 kg of carbon nanotubes and NASICON structure LATP solid electrolyte powder (LATP chemical formula is Li 1.3 Al 0.3 Ti 1.7 (PO4)3), lithium cobalt oxide is used as a raw material, and is placed in a magnetic stirrer with deionized water, stirred and mixed evenly to obtain a mixed solution with a solid content of 26%; wherein the content of each material in the raw material is: 4wt% of carbon nanotubes, 4wt% of NASICON structure LATP solid electrolyte powder, and 92wt% of lithium cobalt oxide; the particle size Dv50 of lithium cobalt oxide is 15μm, the particle size Dv50 of NASICON structure LATP solid electrolyte is 500nm; the particle size Dv50 of graphite is 400nm.

[0082] (2) The mixed solution was placed in a forced air drying oven at 150° C. for 6 hours to obtain a precursor material.

[0083] (3) The precursor material is placed in a rotary furnace, heated to 200°C at a heating rate of 5°C / min, and the excess solvent is removed after pre-sintering for 5 hours. The temperature is then raised to 900°C at a heating rate of 5°C / min, and kept at this temperature for 12 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0084] The high-rate lithium-ion battery positive electrode material prepared in this embodiment was used to prepare positive electrode sheets and assembled into button batteries for testing. The battery assembly and cycle testing methods were the same as in Example 1. The cycle capacity retention rate after 100 test cycles is shown in Table 1.

[0085] Example 5

[0086] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0087] (1) A total of 1 kg of sucrose and garnet structure LLZTO solid electrolyte powder (chemical formula: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ), lithium iron manganese phosphate ternary material as raw material, placed in a magnetic stirrer with ethanol, stirred and mixed evenly to obtain a mixed solution with a solid content of 25%; wherein the content of each material in the raw material is: 7wt% of sucrose, 7wt% of garnet structure LLZTO solid electrolyte powder, 86wt% of lithium iron manganese phosphate ternary material; the particle size Dv50 of the lithium iron manganese phosphate ternary material is 1.3μm, the particle size Dv50 of the garnet structure LLZTO solid electrolyte is 100nm; the particle size Dv50 of sucrose is 100nm.

[0088] (2) The mixed solution was placed in a forced air drying oven at 100° C. for 15 hours to obtain a precursor material.

[0089] (3) The precursor material is placed in a box furnace, heated to 200°C at a heating rate of 2°C / min, and the excess solvent is removed after pre-sintering for 3 hours. The temperature is then raised to 900°C at a heating rate of 2°C / min, and kept at this temperature for 10 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0090] Example 6

[0091] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0092] (1) 1 kg of graphite and NASICON structure LAGP solid electrolyte powder (chemical formula: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12), lithium manganate as a raw material, and N-methyl pyrrolidone are placed in a magnetic stirrer, stirred and mixed evenly to obtain a mixed solution with a solid content of 30%; wherein the content of each material in the raw material is: 5wt% of graphite, 7wt% of NASICON structure LAGP solid electrolyte powder, and 88wt% of lithium manganate; the particle size Dv50 of lithium manganate is 15μm, the particle size Dv50 of NASICON structure LAGP solid electrolyte is 200nm; the particle size Dv50 of graphite is 100nm.

[0093] (2) The mixed solution was placed in a forced air drying oven at 250° C. for 15 hours to obtain a precursor material.

[0094] (3) The precursor material is placed in a box furnace, heated to 300°C at a heating rate of 5°C / min, and the excess solvent is removed after pre-sintering for 2 hours. The temperature is then raised to 800°C at a heating rate of 5°C / min, and kept at this temperature for 12 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0095] Example 7

[0096] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0097] (1) A total of 1 kg of carbon nanotubes and perovskite structure LLTO solid electrolyte powder (chemical formula Li 0.33 La 0.56 TiO3) and lithium nickelate are used as raw materials, placed in a magnetic stirrer with tetrahydrofuran, stirred and mixed evenly to obtain a mixed solution with a solid content of 55wt%; wherein the content of each material in the raw materials is: 6wt% of carbon nanotubes, 4wt% of perovskite structure LLTO solid electrolyte powder, and 90wt% of lithium nickelate; the particle size Dv50 of lithium nickelate is 5μm, the particle size Dv50 of perovskite structure LLTO solid electrolyte is 100nm; the particle size Dv50 of carbon nanotubes is 100nm.

[0098] (2) The mixed solution was placed in a vacuum drying oven and dried at 80° C. for 10 hours to obtain a precursor material.

[0099] (3) The precursor material is placed in a rotary furnace, heated to 150°C at a heating rate of 5°C / min, pre-sintered for 2 hours to remove excess solvent, and then heated to 750°C at a heating rate of 5°C / min, kept at this temperature for 15 hours, and cooled to room temperature to obtain a high-rate lithium-ion battery positive electrode material.

[0100] Example 8

[0101] This embodiment provides a preparation process and performance test of a high-rate lithium-ion battery positive electrode material, and the specific process is as follows.

[0102] (1) 1 kg of phenolic resin and NASICON structure LATP solid electrolyte powder (LATP chemical formula is Li 1.3 Al 0.3 Ti 1.7 (PO4)3), lithium iron phosphate is used as a raw material, and acetone is placed in a magnetic stirrer, stirred and mixed evenly to obtain a mixed solution with a solid content of 60%; wherein the content of each material in the raw material is: 4wt% phenolic resin, 4wt% NASICON structure LATP solid electrolyte powder, 92wt% lithium iron phosphate; the particle size Dv50 of lithium iron phosphate is 2μm, the particle size Dv50 of NASICON structure LATP solid electrolyte is 200nm; the particle size Dv50 of phenolic resin is 200nm.

[0103] (2) The mixed solution was placed in a forced air drying oven at 60° C. for 10 hours to obtain a precursor material.

[0104] (3) The precursor material is placed in a rotary furnace, heated to 150°C at a heating rate of 5°C / min, and the excess solvent is removed after pre-sintering for 4 hours. The temperature is then raised to 900°C at a heating rate of 5°C / min, and kept at this temperature for 12 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained.

[0105] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with embodiments 1 and 3.

[0106] Comparative Example 1

[0107] This comparative example provides a preparation process and performance test of a lithium cobalt oxide positive electrode material coated with an oxide solid electrolyte. The difference from Example 1 is that the coating layer on the surface of the lithium cobalt oxide does not contain carbon. The specific process is as follows:

[0108] (1) A total of 1 kg of perovskite structure LLTO solid electrolyte powder (chemical formula: Li 0.33 La 0.56 TiO3) and lithium cobalt oxide as raw materials, are placed in a magnetic stirrer with deionized water, stirred and mixed evenly to obtain a mixed solution with a solid content of 30wt%; wherein the content of each material in the raw materials is: 14wt% of perovskite structure LLTO solid electrolyte powder, 86wt% of lithium cobalt oxide; the particle size Dv50 of lithium cobalt oxide is 15μm.

[0109] The processes of step (2) and step (3) are the same as those in Example 1.

[0110] The lithium cobalt oxide positive electrode material coated with the oxide solid electrolyte of this comparative example is used to prepare a positive electrode plate and assembled into a button battery. The preparation method of the plate and the assembly method of the battery are the same as those in Implementation 1.

[0111] The button cell assembled in this comparative example was subjected to a cycle test according to the test method of Example 1, and the cycle curve obtained was as follows: Figure 2 As shown, it can be seen that the capacity retention rate of the button-type battery prepared using the positive electrode material of the lithium ion battery in Example 1 after 100 cycles is significantly higher than that of the button-type battery in Comparative Example 1, indicating that the button-type battery prepared using the positive electrode material of the lithium ion battery in Example 1 has better cycle performance. The cycle capacity retention rate after 100 cycles of the test is shown in Table 1.

[0112] The button cell assembled in this comparative example was subjected to rate performance test according to the test method of Example 3, and the obtained rate cycle test graph is as follows: Figure 3 As shown, it can be seen that the specific capacity of the button-type battery assembled in Example 1 at different current densities is higher than that of the battery in Comparative Example 1, indicating that the button-type battery prepared using the lithium-ion battery positive electrode material of Example 1 has better rate performance.

[0113] Comparative Example 2

[0114] This comparative example provides a preparation process and performance test of a carbon-coated lithium cobalt oxide positive electrode material. The difference from Example 1 is that the coating layer on the surface of the lithium cobalt oxide does not contain an oxide solid electrolyte. The specific process is as follows:

[0115] (1) 1 kg of graphite and lithium cobalt oxide as raw materials are placed in a magnetic stirrer with deionized water, and stirred and mixed evenly to obtain a mixed solution with a solid content of 22%; wherein the content of each material in the raw materials is: 15 wt% of graphite, 85 wt% of lithium cobalt oxide; and the particle size Dv50 of the lithium cobalt oxide is 17.3 μm.

[0116] The processes of step (2) and step (3) are the same as those in Example 3.

[0117] The carbon-coated lithium cobalt oxide positive electrode material of this comparative example is used to prepare positive electrode sheets and assembled into button batteries. The preparation method of the electrode sheets and the assembly method of the batteries are the same as those in Implementation 1.

[0118] The method of the cycle test is the same as that of Example 1. The cycle capacity retention rate after 100 test cycles is shown in Table 1.

[0119] The button cell assembled in this comparative example was subjected to rate performance test according to the test method of Example 3, and the obtained rate cycle test graph is as follows: Figure 3As shown, it can be seen that the button-type battery prepared using the lithium-ion battery positive electrode material of Example 3 has a higher specific capacity at different current densities than the battery of Comparative Example 2, indicating that the button-type battery prepared using the lithium-ion battery positive electrode material of Example 3 has better rate performance.

[0120] Table 1 is a summary of the cycle capacity retention rate data of the batteries assembled in Examples 1-4 and Comparative Examples 1-2 after 100 cycles:

[0121] serial number Capacity retention rate after 100 cycles Example 1 86.85% Example 2 85.29% Example 3 84.72% Example 4 85.92% Comparative Example 1 75.46% Comparative Example 2 73.93%

[0122] Table 1 From Table 1, it can be seen that the cycle capacity retention rate of the batteries assembled in Examples 1-4 after 100 cycles is higher than that of Comparative Examples 1-2, indicating that the cycle performance of the batteries containing lithium ion positive electrode materials in Examples 1-4 of the present invention is better than that of Comparative Examples 1-2. This is because the lithium ion battery positive electrode material of the present invention can simultaneously give play to the good ionic conductivity of the oxide solid electrolyte and the good electronic conductivity of carbon, thereby enhancing the rate performance and cycle stability of the positive electrode active material.

[0123] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high-rate lithium-ion battery positive electrode material, characterized in that: The preparation method comprises: Placing the carbon source material, the oxide solid electrolyte, the positive electrode active material and the solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution; placing the mixed solution in a drying device for drying to obtain a precursor material; The precursor material is placed in a sintering device, pre-sintered at 150°C-300°C for 2 hours-6 hours, and after removing excess solvent, the temperature is further raised to 400°C-900°C, and sintered at this temperature for 6 hours-24 hours. After cooling to room temperature, a high-rate lithium-ion battery positive electrode material is obtained; The positive electrode active material includes: one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials.

2. The preparation method according to claim 1, characterized in that: The particle size Dv50 of the positive electrode active material is between 0.3 μm and 50 μm; The carbon source material includes: one or more of carbon fiber, carbon nanotube, graphene, sucrose, starch, graphite, phenolic resin, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, epoxy resin; the particle size Dv50 of the carbon source material is between 100nm and 800nm; The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte; the particle size Dv50 of the oxide solid electrolyte is between 100nm and 800nm; The solvent includes: one or more of deionized water, ethanol, N-methylpyrrolidone, acetone, chloroform, benzene, styrene, and tetrahydrofuran; The mass ratio of the positive electrode active material, the carbon source material and the oxide solid electrolyte material in the mixed solution is [0.65-0.95]: [0.001-0.2]: [0.001-0.2]; The solid content of the mixed solution is 10%-65%.

3. The preparation method according to claim 1, characterized in that: The stirring equipment includes: one or more of a VC high-efficiency mixer, a magnetic stirrer, a vertical stirring tank, a high-speed mixer, and a planetary stirring mixer.

4. The preparation method according to claim 1, characterized in that: The drying equipment includes: one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying treatment temperature is 60° C.-300° C.; and the drying time is 6 hours-24 hours.

5. The preparation method according to claim 1, characterized in that: The sintering equipment includes: any one of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln; The heating rate of the sintering equipment is set at 2°C / min-10°C / min.

6. A high-rate lithium-ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The high-rate lithium-ion battery positive electrode material comprises a positive electrode active material and a composite coating layer coated on the outer surface of particles of the positive electrode active material; the composite coating layer comprises carbon and an oxide solid electrolyte; The positive electrode active material includes: one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium manganese iron phosphate ternary materials.

7. The high-rate lithium-ion battery positive electrode material according to claim 6, characterized in that: The mass of the carbon accounts for 0.1%-20% of the total mass of the positive electrode material of the lithium-ion battery; The mass of the oxide solid electrolyte accounts for 0.1%-20% of the total mass of the lithium-ion battery positive electrode material; The oxide solid electrolyte includes: one or more of a perovskite solid electrolyte, a NASICON solid electrolyte, a LISICON solid electrolyte, and a garnet solid electrolyte.

8. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the high-rate lithium-ion battery positive electrode material as described in claims 6-7, a conductive agent and a binder.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet, the negative electrode sheet, the electrolyte or the solid electrolyte, and the separator as described in claim 8.

10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery includes any one of a liquid lithium-ion battery, a condensed lithium-ion battery, a polymer lithium-ion battery or an all-solid lithium-ion battery.

Citation Information

Cited By

  • One-core dual-coated battery positive electrode material, preparation method and battery

    CN120565650A

  • Negative electrode material and preparation method and application thereof

    CN120622443A

  • Positive plate, manufacturing method thereof and secondary battery

    CN120933376A

  • Positive electrode sheet, method for manufacturing the same, and secondary battery

    CN120933376B

  • Carbon-coated high-entropy oxide composite material as well as preparation method and application thereof

    CN120955125A